1976
DOI: 10.1111/j.1475-4991.1976.tb01138.x
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of Different Methods of Estimating Equivalence Scales and Their Results

Abstract: This paper discusses the problems encountered in constructing equivalence scales of the relative incomes required to enable families of different sizes or in different circumstances to enjoy the same standard of living. Theoretical problems and limitations of various methods are discussed, and examples of empirical results are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
3

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 5 publications
0
32
0
3
Order By: Relevance
“…(For relatively recent examples, see Blackorby and Donaldson, 1989;Blundell, Pashardes andWeber 1989, 1984;Deaton, et al, 1989;Johnson and Garner, 1993;Jorgenson and Slesnick, 1987;Lewbel, 1989a and 19893;Nelson, 1992;Phipps, 1990;Ray, 1986.) Unfortunately, no consensus has emerged about how best to estimate equivalence scales (or even if it is possible to estimate equivalence scales-see Nicholson, 1976;Pollak and Wales, 1979;Blundell and Lewbel, 1991). Yet, scales are essential to the design, implementation and evaluation of almost all tax and transfer policies-scales, at least implicitly, are in use every day.…”
mentioning
confidence: 99%
“…(For relatively recent examples, see Blackorby and Donaldson, 1989;Blundell, Pashardes andWeber 1989, 1984;Deaton, et al, 1989;Johnson and Garner, 1993;Jorgenson and Slesnick, 1987;Lewbel, 1989a and 19893;Nelson, 1992;Phipps, 1990;Ray, 1986.) Unfortunately, no consensus has emerged about how best to estimate equivalence scales (or even if it is possible to estimate equivalence scales-see Nicholson, 1976;Pollak and Wales, 1979;Blundell and Lewbel, 1991). Yet, scales are essential to the design, implementation and evaluation of almost all tax and transfer policies-scales, at least implicitly, are in use every day.…”
mentioning
confidence: 99%
“…This does not mean, however, that families with the same budget share for some particular good (food or anything else) necessarily receive the same utility. It can even be argued that using the share of the budget devoted to food as an indicator of well-being tends to overestimate the true cost of children [4].…”
Section: The Engel Methods and Its Generalizationsmentioning
confidence: 99%
“…31 Hours spent in household production would imply that "puzzles" would exist for other private goods in the past that have time as a signi…cant input, or at least a case must be made for why food would be di¤erent from other time intensive processes. 32 In general, empirical identi…cation of the relevant factors from such models will be di¢ cult given the historical data.…”
Section: @O @Nmentioning
confidence: 99%
“…2 As such, it has served as the model used by Deaton and Paxson (1998) and the basis for those who have attempted to resolve the puzzle they discovered and others more generally concerned with public and private For convenience, one good is completely private, f (food), and the other is completely public, h 1 Nicholson (1976) has shown that Engel's method cannot be used to calculate child equivalence scales and Deaton (1997) notes deeper theoretical problems with the Engel methodology, but Perali (2001Perali ( , 2002 argues that the puzzle is a problem of functional form. He concedes, however, that more theoretical research on household economies of scale is needed because "the literature on household economies of scale is not fully developed in the sense that the concept of economies of scale in the household does not have a close analog to the traditional concept de…ned in production theory."…”
Section: The Barten Modelmentioning
confidence: 99%